Kinerja Lama Pemuasaan Terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Nila (Oreochromis niloticus) - Raudhatul Balqis (Fakultas Pertanian Universitas Samudra, 2021)
Tilapia fish is one of the freshwater fish that are widely cultivated in all corners of the country and become a fairly popular consumption fish. Fish growth can be triggered by good feeding. To reduce feed costs and accelerate growth, a feeding strategy is required through periodic feeding or flavoring restrictions. This study aims to determine the long-standing effect of flavoring on the growth and survival of periodically satisfied Tilapia (Oreochromis niloticus). The method used in the study was the RAL Experiment Method (Complete Random Design) with 4 treatments and 3 replays. The flavoring treatment used is P Without flavoring (control) P₂ 1 day fasting 1 day given feed P 1 day fasting 2 days given feed P₄ 1 day fasting 3 days given feed. Each treatment uses seeds measuring 5-6 cm. The observed parameters are Absolute Weight Growth, Absolute Length Growth, Daily Growth Rate, Survival, and Feed Efficiency. The results of the study based on Sidik Ragam Analysis obtained the results that flavoring in tilapia has a real effect (P<0.05) on absolute weight growth and daily growth rate and has no real effect on absolute length growth, survival, and feed efficiency. The best treatment of periodic flavoring is in the treatment of P3 = 1 day of fasting two days given feed